PERUBAHAN SOSIAL EKONOMI PADA SUKU AKIT DI DESA JANGKANG KECAMATAN BANTAN KABUPATEN BENGKALIS - Rozi, M. Syahrul; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Bantit District Akit was once an isolated tribe and underdeveloped from the economic aspect, for that the Bengkalis Regency Government made various efforts to empower the Akit tribe by carrying out various programs and policies to improve the living standards of the Akit tribe community. In addition to relocating the residence of the Bengkalis Regency Government, it also provides several facilities for the community including houses of worship, educational facilities (primary schools), and health facilities in the form of Polindes. The purpose of this study is to determine the characteristics of the Akit in the Jangkang Village and to determine the forms of socio-economic change in the Akit community. This research was conducted in This study was carried out in Hamlet 3 of Jangkang Village, Bantan District, Bengkalis Regency. The population in this study were all people in Hamlet 3 of Jangkang Village. For the sample the authors took 50% of the KK from the Akit Tribe, from the 102 existing KK, the writer took as many as 51 KK to be sampled using random sampling techniques, while the Camat was used as the Key Informant, the data needed, including primary data and secondary data. Data collection techniques were carried out by interviewing, observing and studying literature. Data analysis method used in this research is descriptive qualitative analysis method. From the results of the study concluded: (1) Characteristics of the Akit Hamlet community of Village 3 Jangkang seen from the age of most respondents were respondents aged 36-40 years (49.03%), for education most respondents were uneducated and did not complete elementary school (45.10%), while the religion of the respondents most of the respondents have Islam (47.05%), for the main occupation of the respondents most of the Akit respondents have jobs as farm laborers (58.82%) Characteristics of the Akit community seen from income most of the people have income of around Rp. 1,000,000 - Rp. 2,000,000 (39.22%), for the number of family members, most respondents had family members of 4 - 6 people (31.37%), social change, namely the existence of religious activities and community activities, economic changes due to working hours and increased income. Keywords: Socio-economic Change, Akit Tribe